PERILAKU RITUAL MITIS ABDI DALEM KERATON KASUNANAN SURAKARTA (Sebuah Dialektika Sosiologi Budaya) - R. Adi Prabowo (Pascasarjana Institut Seni Indonesia Surakarta, 2012)
The palace, or keraton, which is recognized as a Javanese cultural centre, requires rituals in order to increase itsspiritual power and also to be used as ameans of preserving the Javanese culture. The courtiers in the keraton, whoare a subservient social group (acting as servants), have a greater portion in the spiritual actions that take place insidethe keraton environment. They are the true executors of this culture since in carrying out their duties, they have nodesire formaterial reward; they wish only for blessings fromGod – their source of power and strength. These acts ofdedication and surrender provide a large contributionto the keraton, and are not only a vehicle for cultural legitimacybut also contain noble and honourable teachings for the benefit of society. This cultural phenomenon was chosen asthe topic to be analyzed froma sociological and cultural approach, with the aimof gaining an understanding of thestructure andway of thought of the executors of this culture. It is hoped that this paperwill provide knowledge andinformation about an original Javanese cultural practicewhich continues to exist and develop to this day, and is stillrelevant to be implemented as a ritual cultural teaching.Keywords: Courtiers, keraton, ritual.